Lipoprotein-Associated Phospholipase A2 Activity as Potential Biomarker of Vascular Dementia - Giovanni Zuliani; Judit Marsillach; Alessandro Trentini; Valentina Rosta; Carlo Cervellati (Antioxidants, 2023)
A wealth of evidence suggests that Lipoprotein-associated phospholipase A2 (Lp-PLA2) plays a relevant role in atherogenesis and inflammation, which in turn are associated with the risk of developing dementia. The aim of this study was to evaluate whether serum Lp-PLA2 activity might be an early and/or late biomarker for different forms of dementia. Serum Lp-PLA2 activity was assessed in older patients with mild cognitive impairment (MCI, n = 166; median clinical follow-up = 29 months), Late-Onset Alzheimer’s disease (LOAD, n = 176), vascular dementia (VAD, n = 43), dementia characterized by an overlap between LOAD and VAD (AD-VAD MIXED dementia) (n = 136), other dementia subtypes (n = 45), and cognitively normal controls (n = 151). We found a significant trend towards higher levels of Lp-PLA2 activity in VAD compared with the other groups (ANOVA, p = 0.028). Similarly, Lp-PLA2 activity was greater in MCI converting to VAD compared with those that did not or did convert to the other types of dementia (ANOVA, p = 0.011). After adjusting for potential confounders, high levels of Lp-PLA2 activity were associated with the diagnosis of VAD (O.R. = 2.38, 95% C.I. = 1.06–5.10), but not with other types of dementia. Our data suggest that increased serum Lp-PLA2 activity may represent a potential biomarker for the diagnosis of VAD.